Odpowiedź :
Odpowiedź:
A) 8 a + (4 a - 7) = 8 a + 4 a -7 = 12 a -7
B) 5 a - (3 a + 6) = 5 a - 3 a -6 =2 a -6
C) - 8 m + (2 n - m) = - 8 m + 2 n - m = - 9 m + 2 n
D) - 3 p - (6 r - 4 p) = - 3 p - 6 r + 4 p = p - 6 r
E) 2 x - 7 y + (5 x - 2 y) = 2 x -7 y +5 x-2 y = 7 x - 9 y
F) 2 x - 7 y + (5 x - 2 y) = 2 x - 7 y + 5 x - 2 y = 7 x - 9 y
G) (3 u - 6 v) + (6 v - 5) = 3 u - 6 v + 6 v - 5 = 3 u - 5
H) (8 u + 3 v) - (2 u + 5 v) = 8 u + 3 v - 2 u - 5 v = 6 u - 2 v
I) ( - a - 4 b) + (5 b - a) = - a - 4 b +5 b - a = -2 a + b
J) (7 a - b) - (4 a - 2 b) = 7 a - b - 4 a + 2 b = 3 a + b
Szczegółowe Wyjaśnienie:
Nie wiem czy dobrze ale nie dawno miałam to.